365 days of wonder : Mr. Browne's precepts - Palacio, R. J. (New York : Alfred A. Knopf, 2014)
August Pullman stole the hearts of over a million readers in the bestselling, award-winning WONDER. 365 DAYS OF WONDER is a beautiful companion to the novel: a collection of quotes and wise words, one for every day of the year. It includes funny, insightful, inspiring thoughts from WONDER's fans, famous authors and personalities - from Roald Dahl and Paul McCartney to Anne Frank, Tolkien and Popeye - and from the novel itself. It's the perfect gift for anyone who loved WONDER, and it's a book to be treasured and enjoyed again and again.
Keywords: Conduct of life -- Quotations, maxims, etc; Quotations -- Juvenile literature; Maxims -- Juvenile literature